A horizon scan of global biological conservation issues for 2022. (January 2022) - Sutherland, William J.; Atkinson, Philip W.; Butchart, Stuart H.M.; Capaja, Marcela; Dicks, Lynn V.; Fleishman, Erica; Gaston, Kevin J.; Hails, Rosemary S.; Hughes, Alice C.; Le Anstey, Becky; Le Roux, Xavier; Lickorish, Fiona A.; et al.
Abstract : We present the results of our 13th annual horizon scan of issues likely to impact on biodiversity conservation. Issues are either novel within the biological conservation sector or could cause a substantial step-change in impact, either globally or regionally. Our global panel of 26 scientists and practitioners identified 15 issues that we believe to represent the highest priorities for tracking and action. Many of the issues we identified, including the impact of satellite megaconstellations and the use of long-distance wireless energy transfer, have both elements of threats and emerging opportunities. A recent state-sponsored application to commence deep-sea mining represents a significant step-change in impact. We hope that this horizon scan will increase research and policy attention on the highlighted issues. Highlights: Our 13th annual horizon scan identified 15 emerging issues of concern for global biodiversity conservation. A panel of 26 scientists and practitioners submitted a total of 80 topics that were ranked using a Delphi-style technique according to the novelty and likelihood of impact on biodiversity conservation. The top 36 issues were discussed at an online meeting held in September 2021 during which issues were ranked according to the same criteria. Our 15 issues cover impacts ranging from satellite megaconstellations to deep-sea mining. Other emerging issues include floating photovoltaics, long-distance wireless energy, and ammonia as a fuel source.